Optimising sink-connected barrier coverage in wireless sensor networks. (2015) - Lai, Yung-Liang; Jiang, Jehn-Ruey
This paper proposes an algorithm, named the optimal node selection algorithm (ONSA), to solve the sink-connected barrier coverage optimisation problem, which is concerned with how to select randomly deployed sensor nodes of a wireless sensor network (WSN) to reach two optimisation goals: 1) to maximise the degree of barrier coverage with the minimum number of detecting nodes; 2) to make the detecting nodes sink-connected with the minimum number of forwarding nodes. The detecting nodes are those for detecting intruders crossing a belt-shaped area of interest. On detecting intruders, they send intruding event notifications to one of the sink nodes with the help of the forwarding nodes to relay the notifications. We prove the optimality of ONSA, analyse its time complexity, perform simulations for it, and compare the simulation results with those of a related algorithm to show ONSA's advantages.